2015
DOI: 10.18063/ijps.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and control of hypertension in the elderly populations of Japan and the United States

Abstract: The Japanese have the highest life expectancy in the world while the United States (U.S.) has relatively low life expectancy. Furthermore, the Americans have relatively poorer health compared to the Japanese. Examination of the treatment of specific conditions such as hypertension in these two countries may provide insights into how the health care system contributes to the relative health in these two countries. In this study, we focus on the treatment of hypertension, as this is the most common condition req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Findings from studies conducted in countries with more developed healthcare systems and advanced screening processes such as Japan, Korea, England, Ireland, Egypt, Brazil and the USA were also found to have lower levels of undiagnosed hypertension than Nepal as found in this study. [40][41][42][43][44][45][46] The prevalence of undiagnosed hypertension in Nepal is relatively closer with that of Bangladesh. 19 This might be due to the less advanced healthcare systems of these two countries with both countries displaying low Health Care Index values.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from studies conducted in countries with more developed healthcare systems and advanced screening processes such as Japan, Korea, England, Ireland, Egypt, Brazil and the USA were also found to have lower levels of undiagnosed hypertension than Nepal as found in this study. [40][41][42][43][44][45][46] The prevalence of undiagnosed hypertension in Nepal is relatively closer with that of Bangladesh. 19 This might be due to the less advanced healthcare systems of these two countries with both countries displaying low Health Care Index values.…”
Section: Discussionmentioning
confidence: 99%
“…Large, longitudinal studies including the Honolulu-Asia Aging Study (HAAS) [6] and the International Population Study on Macronutrients and Blood Pressure (INTERMAP) Study [7] have explored factors that affect metabolic risk as well as how cardiovascular risk factors may affect other health outcomes including dementia and cognitive impairment across Japanese, American, and other populations. Broadly, these studies have found a higher prevalence of metabolic diseases and conditions in the U.S compared to Japan, including higher body mass index (BMI) [8], diabetes [9], atherosclerosis [10], cardiovascular disease mortality [11], as well as higher blood cholesterol levels [12] and a differing prevalence of hypertension [13,14]. Lifestyle factors play key roles in mediating these differences [15].…”
Section: Introductionmentioning
confidence: 99%